Arthrodesis-performing surgical interventions in orthopaedic oncology - Dedkov, Anatoliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The functional abilities of their extremities after arthrodesing interventions for bone tumours were studied in 36 patients. Due to their low functional results, arthrodesing interventions on the knee and hip joints can be used as secondary methods of reconstruction. In order to reconstruct postoperative defects in the distal tibia, arthrodesis of the ankle joint along with arthroplasty can be used. Humeroscapular arthrodesis is the most functional reconstruction method for restoring a partial function in the shoulder joint after Tikhov-Linberg (type B) resection.